EXPLORING CULTURAL VALUES IN THE SILAMPARI MYTH FOR CHARACTER EDUCATION DEVELOPMENT - Maria, Leni; Kasmaini (Faculty of Letters Universitas Balikpapan, 2026)
Folklore serves as an important medium for transmitting cultural values across generations, yet many local narratives are increasingly neglected by younger communities. One of these is the Silampari Myth from Lubuklinggau, which has not been widely examined for its educational potential. To address this gap, this study analyzes the cultural values contained in the Silampari myth as an alternative material for character education. The research employed a qualitative descriptive method. The data were obtained from local folktales in Lubuklinggau City in the form of cultural values found in the Silampari myth, which include the nature of human life (MH), the nature of human work (MK), the nature of human relationships (MM), the nature of human time (MW), and the nature of human–nature relationships (MA). The results indicate that the cultural values reflected in the Silampari myth include honesty, tolerance, democratic attitudes, hard work, conflict avoidance or peacefulness, building friendship, and responsibility. Based on these cultural values, the Silampari myth can serve as an alternative material for character education, considering that the values it contains are aligned with national cultural and character values.